Structures Congress 2017 2017
DOI: 10.1061/9780784480427.042
|View full text |Cite
|
Sign up to set email alerts
|

The Citizen Engineer: Urban Infrastructure Monitoring via Crowd-Sourced Data Analytics

Abstract: In the US, the challenges of an aging infrastructure network, coupled with requirements for maintaining continuous functionality of this network, highlights the need for innovative, and multidisciplinary solutions aimed at the timely detection and remediation of defects and deterioration before serious failure situations materialize. Considering the constant and widespread interactions of citizens with urban infrastructure systems, and the increasing ubiquity of mobile and personal electronic devices equipped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 44 publications
(32 reference statements)
0
15
0
Order By: Relevance
“…of the motivation methods (Harris et al 2017). The results of the survey carried out in the present study revealed that 77.8% of facility management personnel were opposed to offering incentives to the volunteer participants.…”
Section: R a F Tmentioning
confidence: 51%
“…of the motivation methods (Harris et al 2017). The results of the survey carried out in the present study revealed that 77.8% of facility management personnel were opposed to offering incentives to the volunteer participants.…”
Section: R a F Tmentioning
confidence: 51%
“…To overcome these issues, a new path that utilizes crowdsourcing data has attracted increasing interests from researchers in recent years. [9][10][11] Owing to the development of wireless technologies and Internet of things, almost everyone has at least one smart device which is able to connect to the Internet. These smart devices are usually equipped with various sensors, such as accelerometer, camera, gyroscope, and GPS.…”
Section: Introductionmentioning
confidence: 99%
“…These categories are: geometry in the distance domain, geometry in the spectral domain, the effect in distance domain; and geometry and effect in the distance domain. Among them, the International Roughness Index (IRI) proposed by Sayers in [61] is considered as a standard index for road roughness evaluation. IRI was implemented in several standards such as [62] and [63] and has been recognised worldwide [64].…”
Section: Vehicle Dynamic Response Approach For Road Surface Evaluationmentioning
confidence: 99%
“…Figure 2-3: IRI model by a 2-DOF QCS [61] As for the bus, the relationship between road unevenness/vibration and perceived comfort has been the subject of studies over the years [65]. There are many factors affecting passenger perceived comfort, both objective and subjective, as summarised in Figure 2-4.…”
Section: Vehicle Dynamic Response Approach For Road Surface Evaluationmentioning
confidence: 99%
See 1 more Smart Citation